Functional Assessments and Histopathology of Hepatorenal Tissues of Wistar Rats Infused with Carbon Tetrachloride and Treated with Raw and Hydrothermal Processed Herbs - Ojiako, Okey A; Chikezie, Paul C; Ukairo, Doris I; Ibegbulem, Chiedozie O; Nwaoguikpe, Reginald N (Pharmacognosy Communications)
Background and Aim: Herbal remedies offer another strategy for allevia- tion of co-existing liver and kidney pathologic conditions. Objective: The present study ascertained the functional integrity of hepatic and renal tis- sues, concurrently with blood lipid patterns, of Wistar rats infused with CCl4 and treated with raw and hydrothermal processed herbs, namely, Monodora myristica, Chromolaena odorata, Buccholzia coriacea and Sphe- nostylis stenocarpa. Materials and Methods: Measurement of phyto- chemical contents of the herbs was according to standard methods. The rats were randomly designated on the basis of diets and treatments re- ceived for 28 consecutive days. Fibrosis was induced in the Wistar rats by single dose intra-peritoneal injection of CCl4 for 2 consecutive days. Liver and kidney function tests and serum lipid profile were measured using spectrophotometric methods. Renal and hepatic tissues were subjected to histopathological examinations. Results: The concentrations of alkaloids in the four herbal extracts were within the range of 4.83 ± 0.03 – 31.33 ± 0.29 mg/100 g sample, whereas the concentrations of saponins varied within a relatively narrow range: 0.33 ± 0.09 – 4.33 ± 0.02 mg/100 g dry sample; p > 0.05. The activity ratios of AST to ALT of the rat groups were generally less than 1.0 unit. Atherogenic indices of fibrotic rats were within the following ranges: TAG/HDL-C ratio (3.59 ± 0.03 – 6.76 ± 0.06), TC/HDL-C ratio (3.72 ± 0.02 – 6.94 ± 0.05) and LDL-C/HDL-C ratio (2.00 ± 0.01 – 4.59 ± 0.02). Conclusion: Losses in phytochemical contents following hydrothermal processing of the herbs did not substantially affect their overall therapeutic scores against morphological and functional impairments of hepatic and renal tissues following CCl4 intoxication of the rats.
Keywords: Carbon tetrachloride; Histopathology; Hydrothermal; Kidney; Liver.